MARKETING MIX FACTORS THAT INFLUENCE THE DECISION TO PURCHASEA PLASTIC - Saengsri, Phitchayada; Visitnitikija, Chinnaso (Journal of MCU Nakhondhat, 2024)
A study of marketing mix factors affecting the decision to purchase a plastic injection molding machine aims to 1) Study the marketing mix factors in deciding to purchase plastic injection molding machines. 2) Study the marketing mix factors that affect the decision to purchase plastic injection machines. A questionnaire was used to collect data, using statistics, percentages, mean, inferential statistics, t-test, f-test (one-way ANOVA), and multiple regression analysis. Findings indicated that most respondents were limited companies with an establishment of 6-10 years, employment of 50-100 employees, registered capital of 6-10 million baht, annual order value of 4-5 million baht, and managing directors. The overall average level of opinions on marketing mix factors was at a moderate level of importance. The average decision-making process for purchasing a plastic injection molding machine is moderate. The different types of establishments, establishment age, number of employees, number registered capital, annual purchase value, and authority person with purchase decision were not affected in buying a plastic injection molding machine. Price influences the purchase of a plastic injection molding machine with statistical significance at the .05 level. The study suggests that business operators should focus on creating a reliable image of their products. Set the price appropriate to the quality of use. Spare parts are guaranteed. Provide equipment, tools, and develop modern technology to build customer confidence.